Curative Conservation Of The Metal Collection At Museum Benteng Vredeburg Yogyakarta - Hariny Puspadewi Sekarlatih; Mikke Susanto; Rr. Vegasari Adya Ratna (Institut Seni Indonesia Yogyakarta, 2023)
Museum Benteng Vredeburg Yogyakarta (MBVY) serves as evidence of prehistoric remnants and commemorates Indonesia's pre-independence struggle. Its diverse collection includes metals possessing historical and artistic value. Metal, prone to corrosion through oxidation, requires preventive measures against various damage agents. This study explores curative conservation practices for corroded metal collections at MBVY. Utilizing a descriptive-qualitative approach, data from observation, interviews, and documentation inform the analysis. Following standards like A Practical Guide to the Care and Conservation of Metal, the research outlines the curative conservation process—proposals, identification, documentation, repetition, monitoring, and evaluation. Challenges, including limited human resources, underscore the importance of adhering to standard operational procedures.